Implementasi Program Pemberdayaan Fakir Miskin Melalui Kelompok Usaha Bersama (Kube) Di Kecamatan Bengkalis - Herniyati Herniyati; Hasim As’ari; Adianto Adianto (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2022)
The development of social welfare is the responsibility of the government and society. The existence of a Joint Business Group (KUBE) for the poor in the community has become one of the policy options to increase productive economic enterprises (especially in increasing income) and the establishment of microfinance institutions. The purpose of this study is to analyze the implementation of the empowerment program for the poor through the Joint Business Group (KUBE) in Bengkalis District and identify the factors that hinder it. This research is a descriptive qualitative research type. The result of this research is that the implementation of the KUBE program carried out in Bengkalis District has not yet achieved optimal results but the implementation of the program is quite effective and successful according to the target for channeling funds to joint business groups